Guía interactiva para la toma de decisiones constitucionales y legales en salud (2020)
According to Law 1751 of 2015, the right to health is autonomous and inalienable, both in its individual and collective sphere, and its provision corresponds to the State. In this regard, there is a dichotomy in the health protection right in its two protection spheres, which occasionally generates conflicting results, especially when it comes to Tutelage actions ( Accion de Tutela) that, when solving individual cases, may include orders to provide services outside the system 's cover and inefficient measures (such as orders to provide complementary social services) which are funded with resources available to guarantee the collective health right, therefore generating impacts that can put the sustainability of the health system at risk. This leads us to question: how to ensure that a tutelage action decision that resolves individual cases in health considers its effect with respect to the collective guarantee of the same fundamental right? This work, through technical, normative and jurisprudential analysis, answers the question by means of an interactive guide that provides tools for judges to issue and resolve health cases..